A Genome-Wide Survey of Date Palm Cultivars Supports Two Major Subpopulations in Phoenix dactylifera. Issue 7 (1st July 2015) - Mathew, Lisa S; Seidel, Michael A; George, Binu; Mathew, Sweety; Spannagl, Manuel; Haberer, Georg; Torres, Maria F; Al-Dous, Eman K; Al-Azwani, Eman K; Diboun, Ilhem; Krueger, Robert R; Mayer, Klaus F X; et al.
Abstract: The date palm ( Phoenix dactylifera L.) is one of the oldest cultivated trees and is intimately tied to the history of human civilization. There are hundreds of commercial cultivars with distinct fruit shapes, colors, and sizes growing mainly in arid lands from the west of North Africa to India. The origin of date palm domestication is still uncertain, and few studies have attempted to document genetic diversity across multiple regions. We conducted genotyping-by-sequencing on 70 female cultivar samples from across the date palm–growing regions, including four Phoenix species as the outgroup. Here, for the first time, we generate genome-wide genotyping data for 13, 000–65, 000 SNPs in a diverse set of date palm fruit and leaf samples. Our analysis provides the first genome-wide evidence confirming recent findings that the date palm cultivars segregate into two main regions of shared genetic background from North Africa and the Arabian Gulf. We identify genomic regions with high densities of geographically segregating SNPs and also observe higher levels of allele fixation on the recently described X-chromosome than on the autosomes. Our results fit a model with two centers of earliest cultivation including date palms autochthonous to North Africa. These results adjust our understanding of human agriculture history and will provide the foundation for more directed functional studies and a better understanding of genetic diversity in date palm.